System kontroli państwowej usytuowanej przy naczelnych organach przedstawicielskich: [System of state control at supreme representations] (Studia Prawnicze / The Legal Studies, 1984)
A methodological assumption of the work was to 'isolate in the process of development of control in socialist states. four basic systems: a) control at representation, b) party and government control, c) government control, d) special control division beyond the administrative apparatus, called Jugoslav system. Then the first system, :i.e. control at representations was presented in details. Polish experience !in the field of organizing the Control Bureau in the period of the National People's Council and Legislative Diet (1944-1949)y Supreme Chamber of Audit on the basis of laws of 1949, 1957 avid 1980 have been recalled. The analysis of basic solutions comprised in those legal acts reveals gradual expansion of powers of the parliament and its organs in relation to the Supreme Chamber of Audit, with diminishing tasks of the Council of State Certain Bulgarian (19741976) and Roumanian (since 1973) experience have been referred to. The problem was called parliamentarization of control. Next, the influence of the system on control authorities situated within administrative structures was presented and a trend to depart, already in the 60s, from playing a role of a classic ministry by a control organ, establishing some connections with representation was presented. As a consequence, control organized as a ministry 'differs a lot from other administrative organs as far as its connections with representations are concerned. which confirms the phenomenon Of its parliamentarization. Juigoslav system was also characterized and the connections of Social Book-Keeping Service of Socialist Federative Republic of Jugoslavia with representations were stressed.